Folklore. - Jacobs, Joseph, 1854-1916,; Nutt, Alfred Trübner, 1856-1910,; Wright, Arthur Robinson, 1862-1932,; Crooke, William, 1848-1923, (1890- : Publications - Folk-lore Society, v. 27-)
Most vols. for 1890- contain list of members of the Folk-lore Society.